2019
DOI: 10.1175/jpo-d-18-0204.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Barrier Layer Formation and Erosion from In Situ Observations in the Bay of Bengal

Abstract: During the Bay of Bengal (BoB) Boundary Layer Experiment (BoBBLE) in the southern BoB, time series of microstructure measurements were obtained at 8 • N, 89 • E from 4-14 July, 2016. These observations captured events of barrier layer (BL) erosion and re-formation. Initially, a three-layer structure was observed: a fresh surface mixed layer (ML) of thickness 10-20 m; a BL below of 30-40 m thickness with similar temperature but higher salinity; a high salinity core layer, associated with Summer Monsoon Current.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…Salinity stratification induced by local precipitation is known to significantly impact upper ocean structure and dynamics, for example, through barrier layer formation and isolation of the surface layer from the thermocline. Subsurface barrier layers of relatively higher salinity in an otherwise thermally homogeneous layer have been well documented (George et al., 2019; Lukas & Lindstrom, 1991; Sprintall, 2019) though the details of how these features are related to well‐defined FWLs has yet to be ascertained. This uncertainty is largely set by the understanding of FWL evolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salinity stratification induced by local precipitation is known to significantly impact upper ocean structure and dynamics, for example, through barrier layer formation and isolation of the surface layer from the thermocline. Subsurface barrier layers of relatively higher salinity in an otherwise thermally homogeneous layer have been well documented (George et al., 2019; Lukas & Lindstrom, 1991; Sprintall, 2019) though the details of how these features are related to well‐defined FWLs has yet to be ascertained. This uncertainty is largely set by the understanding of FWL evolution.…”
Section: Introductionmentioning
confidence: 99%
“…thermocline. Subsurface barrier layers of relatively higher salinity in an otherwise thermally homogeneous layer have been well documented (George et al, 2019;Lukas & Lindstrom, 1991;Sprintall, 2019) though the details of how these features are related to well-defined FWLs has yet to be ascertained. This uncertainty is largely set by the understanding of FWL evolution.…”
mentioning
confidence: 99%
“…An extreme negative IOD event occurred in the summer and fall of 2016, which induces the westerly anomaly and has impact on the upper Ocean of the equatorial eastern Indian Ocean and BOB (Lu et al., 2018). Recent studies show observed strong SMC during June–July 2016 (Vinayachandran et al., 2018) may be related to westerly burst caused by the negative IOD (George et al., 2019; Webber et al., 2018). These studies mainly focus on the intensity and salinity transport of the SMC related to the equatorial waves.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the advection of freshwater by the mesoscale stirring also plays an important role in determining SST over the northern BoB (Buckley et al 2020), as these waters are typically associated with relatively shallow mixed layers. In the southern Bay, measurements have suggested the competing influences of mixing and advection of salty Arabian Sea water in the erosion and reformation of the barrier layer during the southwest monsoon (George et al, 2019;. In particular, George et al (2019) show that maintenance of the barrier layer and the associated maximum depth of mixing was critically dependent on horizontal advection through its impact on stratification.…”
Section: Stirring From the Marginsmentioning
confidence: 99%
“…In the southern Bay, measurements have suggested the competing influences of mixing and advection of salty Arabian Sea water in the erosion and reformation of the barrier layer during the southwest monsoon (George et al, 2019;. In particular, George et al (2019) show that maintenance of the barrier layer and the associated maximum depth of mixing was critically dependent on horizontal advection through its impact on stratification. Surface freshwater input also has an impact on barrier layer evolution; several freshening events were captured at various stages of their seasonal evolution in the southern Bay of Bengal in recent observations .…”
Section: Stirring From the Marginsmentioning
confidence: 99%